Les doctrinaires français et serbes : des idées similaires, des contextes différents – la possibilité d’une réception - Marko Božić (Cahiers Balkaniques)
Abstract: Already detected and appropriately described in the national historiography, traces of doctrinaire liberalism in the tradition of the Serbian legal thought have never been thoroughly analysed from the perspective of their origin and ties with its Western, in particular, French models. A comparative analysis of two doctrinaire discourses, the Serbian and French, conducted by intertwining the text and context of reception, raises a question of a liberal profile of Serbian doctrinaires and their similarity to their French counterparts. The results of the analysis, hence, not only contribute to relativizing the hypothesis of a direct exchange of ideas between the two distant political cultures, one being from the core and other from the periphery of „the world-system“, but also challenge the very possibility of the Western liberalism as a universal model.